Proximal tibial strains following unicompartmental knee arthroplasty (UKA) : a finite element study - Xiao, Xiao (2014)
Stress fracture on the medial tibia plateau following unicompartmental knee arthroplasty (UKA) has been reported for years yet the reason for such occurrences has not been fully understood. Previous indications showed that the strength of the tibia was compromised and the support beneath the implant has deteriorated due to UKA but the origin of such failure is still being studied.